Electrolyte laminate and non-aqueous secondary battery including same
Patent Information
- Application Number
- JP2021011970
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-28
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2041-01-28
AI Technical Summary
【0012】 本発明の電解質積層体を電池セルに適用すれば、電極活物質との界面抵抗及び放電過電圧が顕著に減少し、結果的に十分な放電容量が具現化され、出力特性及びエネルギー密度を改善し、サイクル性を向上させることができる。
Smart Images

Figure 0007638100000003 
Figure 0007638100000004 
Figure 0007638100000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolyte laminate and a nonaqueous secondary battery including the electrolyte laminate. [Background technology]
[0002] Lithium ion secondary batteries are characterized by their light weight, high energy and long life, and are widely used as power sources for portable electronic devices such as notebook computers, mobile phones, digital cameras, video cameras, etc. In addition, with the transition to a society with a low environmental impact, lithium ion secondary batteries are attracting attention as power sources for hybrid electric vehicles (HEVs) and plug-in HEVs (PHEVs), and also in the field of power storage such as residential power storage systems.
[0003] Conventionally, an organic electrolyte solution in which a lithium salt is dissolved in an organic solvent has been used as the electrolyte for lithium ion secondary batteries, and there have been safety concerns associated with leakage.
[0004] All-solid-state batteries, which use a solid electrolyte instead of a liquid electrolyte and make the positive electrode material, electrolyte, and negative electrode material all solid, are proposed as a technology that eliminates the need for flammable electrolyte and dramatically improves safety.
[0005] As oxide-based solid electrolytes for use in all-solid-state batteries, attempts have been made to use metal oxide-based materials such as garnet-type oxides, NASICON-type oxides, or perovskite-type oxides as solid electrolytes. These metal oxide-based materials have lithium ion conductivity and are chemically stable, but have the problem of being hard and poorly moldable. On the other hand, there have been disclosures of technologies using sulfide-based materials due to their high lithium ion conductivity. However, sulfide-based materials have poor chemical stability, and hydrogen sulfide is generated when exposed to the atmosphere, and when the sulfide-based solid electrolyte is directly contacted with the positive electrode material, a "deficiency layer" with a thickness of several nanometers where no lithium exists appears at the interface, resulting in a significant decrease in output characteristics. Compared to metal oxide materials, sulfide-based materials have the advantage of being easier to mold, but on the other hand, their pressing pressure is high and short circuits are likely to occur when pressurized. For this reason, sulfide-based solid electrolytes need to be secured to a certain thickness or more, which is problematic from the viewpoint of increasing the electric capacity of the battery by thinning the solid electrolyte layer and increasing the amount of active material filled.
[0006] In response to the above problems, attention has been focused on solid polymer electrolytes, but all-solid-state batteries using solid polymer electrolytes are difficult to achieve sufficient output or capacity, not only at room temperature but also at 60°C to 80°C. The reasons for this include the low ionic conductivity of the polymer electrolyte, as well as the interface resistance between the electrode active material and the solid polymer electrolyte. Many efforts have been made to solve the problem of the ionic conductivity of solid polymer electrolytes, but there has been no revolutionary improvement in ionic conductivity, and this has been pointed out as the limit of solid polymer electrolytes.
[0007] For example, Patent Document 1 aims to provide a polymer electrolyte for an all-solid-state battery in which the interfacial resistance between lithium and the solid polymer electrolyte is significantly reduced, but when laminating as described in Patent Document 1, it is easy to deform in the in-plane direction. In particular, polymer solid electrolytes with high ionic conductivity are generally highly flexible and often prone to plastic deformation, and deformation during the lamination process is often a problem. In particular, when a highly expandable electrode, for example, an electrode containing a silicon (Si)-based negative electrode active material, is combined with a polymer solid electrolyte, Li is inserted into the Si-based negative electrode active material during charging, causing expansion, an increase in internal pressure, etc., and it is expected that deformation will be further accelerated. However, for the purpose of increasing capacity, an electrode containing a Si-based negative electrode active material is very attractive. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 2018-514929 Summary of the Invention [Problem to be solved by the invention]
[0009] In order to reduce the interfacial resistance between the electrode active material and the solid electrolyte, a material with sufficient plasticity is required. On the other hand, if the plasticity of the material is increased too much, the material will flow and there will be no difference from the organic electrolyte solution that is already in frequent use. In view of this, it is difficult to suppress deformation while obtaining interfacial contact by lamination. Therefore, the present invention aims to provide an electrolyte film that can obtain sufficient interfacial contact while suppressing deformation by using a lithium ion conductor that is solid but can exhibit high ionic conductivity, and a nonaqueous secondary battery including the electrolyte film. [Means for solving the problem]
[0010] The inventors have found that by controlling the various physical properties of the electrolyte laminate constituting the electrolyte film, it is possible to improve the contact between the solid electrolyte and the electrode active material while suppressing deformation, thereby improving ion conductivity, and have completed the present invention. As will be described in detail later, a non-ion-conductive reinforcing layer is present in the second solid electrolyte layer in the electrolyte laminate. When this reinforcing layer comes into contact with the electrode active material, the ion conductivity decreases, so the reinforcing layer is covered with an ion-conductive electrolyte, thereby providing high performance as a battery. It has also been found that it is preferable to remove battery cells in which the electrode active material is in contact with the reinforcing layer at an early stage of conditioning, and one embodiment of the present invention for achieving this is exemplified below.
[0011] [1] An electrolyte laminate comprising at least a first electrolyte layer, a second electrolyte layer, and a third electrolyte layer bonded and laminated in the order described above, the second electrolyte layer being a composite layer of an electrolyte and a base material, and each of the first, second, and third electrolyte layers containing an ion-transporting organic material, The first electrolyte layer and the second electrolyte layer contain different ion-transporting organic materials, and the consistency of the ion-transporting organic material contained in the second electrolyte layer at 25°C is 100 or more and less than 400. [2] The electrolyte laminate according to item 1, wherein the substrate is composed of continuous long fibers. [3] The electrolyte laminate according to item 1 or 2, wherein the substrate is a laminated nonwoven fabric. [4] The laminated nonwoven fabric is composed of at least two layers of laminated nonwoven fabric, including a nonwoven fabric layer (I layer) composed of fibers having a fiber diameter of 0.1 μm or more and less than 4.0 μm, and a nonwoven fabric layer (II layer) composed of fibers having a fiber diameter of 4.0 μm or more and 30.0 μm or less, and has a basis weight of 3.0 g / m. 2 More than 20.0g / m 2 4. The electrolyte laminate according to item 3, wherein the thickness of the electrolyte laminate is less than 100 nm. [5] The electrolyte laminate according to any one of items 1 to 4, wherein the second electrolyte layer is a solid electrolyte layer, and a base material included in the solid electrolyte layer has a decomposition current threshold of 2.0 V or more and 4.5 V (vs. Li) or less. [6] The electrolyte laminate according to any one of items 1 to 5, wherein the substrate is a continuous long-fiber nonwoven fabric or woven fabric composed of at least one selected from the group consisting of polyalkylene terephthalate resins, polyolefin resins, polyamide resins, polyoxymethylene ether resins, polyketone resins, thermoplastic polyimide resins, cellulose resin nonwoven fabrics, glass nonwoven fabrics, and glass cloth. [7] The electrolyte laminate according to any one of items 1 to 6, wherein the ion transporting organic material contains a nitrile group. [8] The electrolyte laminate according to any one of items 1 to 7, which is a solid electrolyte laminate. [9] An electrolyte film comprising the electrolyte laminate according to item 8.
[10] A nonaqueous secondary battery structure comprising a positive electrode, a negative electrode, and the electrolyte laminate according to any one of items 1 to 8 or the electrolyte film according to item 9, a nonaqueous secondary battery structure in which the first electrolyte layer or the third electrolyte layer is formed on the positive electrode, and one of the first electrolyte layer or the third electrolyte layer that is not in contact with the positive electrode is formed on the negative electrode, and the second electrolyte layer is self-supporting between at least one pair of the positive electrode and the negative electrode.
[11] A nonaqueous secondary battery comprising a positive electrode, the electrolyte laminate according to any one of items 1 to 8 or the electrolyte film according to item 9, and a negative electrode laminated in the order listed. Effect of the Invention
[0012] When the electrolyte laminate of the present invention is applied to a battery cell, the interfacial resistance with the electrode active material and the discharge overvoltage are significantly reduced, resulting in a sufficient discharge capacity, improved output characteristics and energy density, and improved cycle performance. [Brief description of the drawings]
[0013] [Figure 1] 1 is a plan view showing an example of the configuration of a nonaqueous secondary battery using an ion conductor according to one embodiment of the present invention; [Diagram 2]2 is a cross-sectional view taken along line AA of the nonaqueous secondary battery of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Below, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail with reference to the drawings. However, the present invention is not limited to the embodiment or drawings described below, and various modifications are possible without departing from the gist of the present invention.
[0015] An example of the nonaqueous secondary battery of this embodiment is shown in Figures 1 and 2. Figure 1 is a plan view that shows a schematic diagram of the example of the nonaqueous secondary battery, and Figure 2 is a cross-sectional view taken along line AA in Figure 1.
[0016] The nonaqueous secondary battery 100 is configured by housing a laminated electrode body formed by laminating a positive electrode 150 and a negative electrode 160 with an electrolyte laminate 170, which is a lithium ion conductor layer, in an area 120 of a laminate film exterior body 110 formed of two aluminum laminate films. The aluminum laminate film exterior body 110 is sealed at its outer periphery by heat fusing the upper and lower aluminum laminate films. The area 120 is a part of the exterior body 110, and is a bulged space for housing the laminate formed of the positive electrode 150, the negative electrode 160, and the electrolyte laminate 170.
[0017] The positive electrode 150 and the negative electrode 160 are electrically connected to an aluminum tab 130 and a nickel tab 140, respectively, for connection to an external circuit. In Fig. 2, in order to avoid complicating the drawing, the layers constituting the aluminum laminate film exterior body 110 and the layers of the positive electrode 150 and the negative electrode 160 are not shown separately. In the nonaqueous secondary battery 100, the members other than the ion conductor may be those provided in conventional lithium ion secondary batteries, and may be, for example, those described below.
[0018] In the non-aqueous secondary battery 100, pressure may be applied within the region 120. The components of the non-aqueous secondary battery are described below.
[0019] Unless otherwise specified, all measurements should be carried out at a room temperature of 25°C and a humidity of 60% RH.
[0020] 1. Electrolyte laminate The electrolyte laminate of this embodiment is formed by sequentially bonding at least a first electrolyte layer, a second electrolyte layer, and a third electrolyte layer. The ion-transporting organic substances that conduct ions contained in the first electrolyte layer, the second electrolyte layer, and the third electrolyte layer may be different from each other, the ion-transporting organic substances contained in any electrolyte layer may be the same, and the ion-transporting organic substances contained in all electrolyte layers may be the same, but it is preferable that at least the first electrolyte layer and the second electrolyte layer contain different ion-transporting organic substances. It is preferable that the ion-transporting organic substances contained in the first electrolyte layer and the third electrolyte layer have compositions that match the electrodes that contact them, and it is preferable that the second electrolyte layer has a composition that matches the conduction of ions from the first electrolyte layer to the second electrolyte layer. In addition to the viewpoint of reinforcing the strength of the electrolyte laminate, it is preferable that the second electrolyte layer contains a base material from the viewpoint of effectively using the external pressure during interface formation for interface formation, improving interface bonding, and suppressing electrolyte deformation.
[0021] The electrolyte battery stack in which the first electrolyte layer, the second electrolyte layer, and the third electrolyte layer are stacked in this order may be in the form of an electrolyte film, and the electrolyte battery stack or the electrolyte film may be a nonaqueous secondary battery component that is self-supportingly disposed between a pair of opposing positive and negative electrodes.
[0022] The electrolyte laminate of the present invention is preferably formed to have a thickness of 5 to 300 μm. The lower limit is preferably thicker in order for the electrolyte laminate to deform and form an interface, more preferably 7 μm or more, and even more preferably 10 μm or more. The upper limit is preferably thinner in order to reduce the amount of deformation during interface formation, more preferably 250 μm or less, and even more preferably 200 μm or less.
[0023] The thickness of each of the first electrolyte layer, the second electrolyte layer, and the third electrolyte layer is not particularly limited, provided that the sum of the layers does not exceed the film thickness of the electrolyte laminate. The thickness of the first electrolyte layer is preferably 1 μm or more and 100 μm or less. The lower limit is preferably thicker in order to allow the electrolyte laminate to deform and form an interface, more preferably 2 μm or more, and even more preferably 3 μm or more. The upper limit is preferably thinner in order to reduce the amount of deformation during interface formation, more preferably 90 μm or less, even more preferably 80 μm or less, and especially preferably 70 μm or less. The thickness of the third electrolyte layer has the same preferred range as the thickness of the first electrolyte layer.
[0024] The thickness of the second electrolyte layer may be preferably 3 μm or more and 100 μm or less. The lower limit is more preferably 4 μm or more, and even more preferably 5 μm or more, in order to maintain the strength of the second electrolyte layer. The upper limit is more preferably 90 μm or less, and even more preferably 80 μm or less, in order to effectively transmit the pressure during the interface bonding to the interface bonding, rather than to the deformation of the second electrolyte layer.
[0025] It is preferable that the permanent strain of the second electrolyte layer is smaller than the permanent strain of the first electrolyte layer and the third electrolyte layer. When the electrolyte layer satisfies the above relationship, the stress at the time of interface formation can be effectively applied to the interface formation, making it possible to form a good interface, and improving the characteristics of the battery using the electrolyte.
[0026] The permanent deformation of electrolytes is generally measured using a microhardness tester. Each electrolyte layer is punched out to a diameter of 5 mm and left to stand for 24 hours under a stress of 0.5 MPa, and the permanent deformation can be calculated from the initial film thickness and the film thickness after 24 hours. When the initial film thickness is Ds and the film thickness after 24 hours is Df, the permanent deformation is calculated using the following formula: (Ds-Df) / Ds It is expressed as:
[0027] The permanent strain of the first electrolyte layer is preferably 0.05 or more and less than 0.90, and the upper limit is more preferably 0.85 or less, even more preferably 0.75 or less, and most preferably 0.70 or less. The lower limit is more preferably 0.10 or more, even more preferably 0.15 or more, and most preferably 0.20 or more. The permanent strain of the third electrolyte layer is preferably in the same range as that of the first electrolyte layer, and the magnitude relationship between the permanent strains of the first electrolyte layer and the third electrolyte layer is not important.
[0028] The permanent strain of the second electrolyte layer is preferably 0.50 or more and 1.00 or less, and the upper limit is more preferably 0.95 or less, further preferably 0.90 or less, and most preferably 0.85 or less. The lower limit is more preferably 0.55 or more, further preferably 0.60 or more, and most preferably 0.65 or more. The permanent strain of the second electrolyte layer is preferably smaller than the permanent strains of the first and third electrolyte layers.
[0029] <1-1. Base material> The substrate as the non-ion conductive reinforcing layer included in the second electrolyte layer is not particularly limited, however, the substrate needs to be porous since it is necessary to contain the electrolyte laminate therein.
[0030] The substrate may be a single layer or a multi-layer laminate of one type of substrate, or a laminate of two or more types of microporous substrates.
[0031] The thickness of the substrate according to the present embodiment is preferably 4 to 100 μm, and there is no problem if it is contained within the second electrolyte layer of the electrolyte laminate. The lower limit is preferably 4 μm or more, more preferably more than 4 μm, and even more preferably 5 μm or more, in order to maintain the strength of the second electrolyte layer. The upper limit is more preferably 90 μm or less, and even more preferably 80 μm or less, in order to effectively transmit the pressure during interface bonding to the interface bonding, rather than to the deformation of the second electrolyte layer.
[0032] The porosity of the substrate is not particularly limited, but is preferably 20% or more and 80% or less. The lower limit is more preferably 30% or more, and even more preferably 40% or more, from the viewpoint of increasing the in-plane strength of the substrate. The upper limit is more preferably 75% or less, and even more preferably 70% or less, from the viewpoint of increasing the ion conduction in the second electrolyte layer.
[0033] When a microporous membrane using a fibrous material is used as the substrate, the weight of the substrate is 2.0 g / m 2 More than 20.0g / m 2 The weight of the substrate is preferably less than 20.0 g / m 2 If the basis weight of the substrate is less than 2.0 g / m, when a certain thickness is required for the substrate, the basis weight of the substrate is not too large and sufficient fiber voids tend to be secured, so that ion permeability can be increased and a high-performance electrolyte laminate can be produced. 2 If the density is equal to or higher than this, the mechanical strength of the slit substrate can be increased, and the substrate tends to have high resistance to tension applied during winding and use after production, making it easier to handle. In order to bond the electrolyte and the electrode interface, the fibers need to be densely present within a certain range. In this sense, the substrate weight is more preferably 3.0 g / m 2 More than 20.0g / m 2 and more preferably 3.0 to 10 g / m 2 It is.
[0034] Any substrate may be used as long as it is self-supporting. Self-supporting refers to a substrate cut into a 10 cm square that does not break under its own weight when held at two vertices. It is preferable that the substrate has a decomposition current threshold of 2.0 V or more and 4.5 V (vs. Li) or less, because when the substrate is in contact with the electrode, it is easy to detect the increase in irreversible capacity during the initial charge / discharge. The decomposition current threshold of the substrate is more preferably 4.3 V (vs. Li) or less, and even more preferably 4.1 V (vs. Li) or less. By having a lower decomposition current threshold, it is possible to hasten the timing of detection. The decomposition current threshold was measured by the linear sweep voltammetry method shown below.
[0035] (Linear sweep voltammetry method) Equal volumes of ethylene carbonate and ethyl methyl carbonate were mixed, and a non-aqueous electrolyte solution with LiPF6 dissolved therein to a concentration of 1M was poured into the battery. 2 The substrate was sandwiched between a circular titanium (Ti) electrode and a Li electrode, and the voltage was swept from the open circuit voltage to a noble voltage of up to 8 V at a sweep rate of 1 mV / sec. The results are plotted as voltage (V) on the horizontal axis and decomposition current (mA / cm) on the vertical axis. 2 ) and the value measured as the x-intercept of the tangent of the rising decomposition current was taken as the decomposition current threshold. 2 The material is sandwiched between a circular Ti electrode and a Li electrode, and the voltage is swept.
[0036] The substrate may be, for example, the same as that provided in known non-aqueous secondary batteries, and is preferably a porous insulating thin film having excellent mechanical strength.
[0037] The substrate is not particularly limited, and examples thereof include woven fabric, nonwoven fabric, (micro)porous film, and glass molded body. Examples of the woven fabric and nonwoven fabric include polyalkylene terephthalate resin (PET, PBT, PTT, etc.) and its derivatives, polyolefin resin (polypropylene, polyethylene, polymethylpentene, etc.) and its derivatives, polyamide resin (N6, N66, N612, etc.) and its derivatives, polyoxymethylene ether resin (POM, etc.), PEN, PPS, PPO, polyketone resin, polyketone resin (PEEK, etc.), thermoplastic polyimide resin (TPI, etc.), aramid resin (polyparaphenylene terephthalamide, etc.), acrylic resin, polyvinyl alcohol resin, cellulose resin (cellulose fiber), etc., alumina fiber, ceramic fiber, glass fiber, or copolymers mainly composed of these resins or fibers, or mixtures thereof, etc.
[0038] In order to further improve hydrophilicity, these substrates may be hydrophilized by a method of adding a surfactant, a method of sulfonation using chemicals such as fuming sulfuric acid and chlorosulfonic acid, a fluorination method, a grafting method, or a method using corona discharge or plasma discharge.
[0039] The substrate is preferably at least one selected from the group consisting of polyalkylene terephthalate resins (PET, PBT, PTT, etc.) and derivatives thereof, polyolefin resins (polypropylene, polyethylene, polymethylpentene, etc.) and derivatives thereof, polyamide resins such as N6, N66, N612, etc. and derivatives thereof; polyoxymethylene ether resins (POM, etc.), polyketone resins such as PEN, PPS, PPO, polyketone resins, PEEK, etc., thermoplastic polyimide resins such as TPI, cellulose resin nonwoven fabrics, glass nonwoven fabrics, and glass cloths. The substrate is more preferably one having a decomposition current threshold of 2.0 V or more and 4.5 V or less (vs. Li), specifically, polyalkylene terephthalate resin (PET, PBT, PTT, etc.) and its derivatives, polyamide resin such as N6, N66, N612, etc. and its derivatives, polyoxymethylene ether resin (POM, etc.), polyketone resin such as PEN, PPS, PPO, polyketone resin, PEEK, etc., thermoplastic polyimide resin such as TPI, etc. Particularly preferred is polyalkylene terephthalate resin (PET, PBT, PTT, etc.) and its derivatives.
[0040] The laminated nonwoven fabric having at least two layers (I layer, II layer) is described below. The nonwoven fabric layer (I layer) is preferably composed of ultrafine fibers having a fiber diameter of 0.1 μm or more and less than 4.0 μm. In this specification, the term "ultrafine fibers" refers to fibers having a fiber diameter in the range of 0.1 μm or more and less than 4 μm. The I layer may contain fibers other than the ultrafine fibers as long as the effect of the present invention is not impaired, but typically consists of only the ultrafine fibers. If the fiber diameter is less than 4.0 μm, the fiber gaps in the nonwoven fabric layer do not become too large, so that the electrolyte easily enters the fiber gaps, resulting in an electrolyte laminate with excellent electrolyte retention. On the other hand, if the fiber diameter is 0.1 μm or more, the fibers can be formed relatively easily, and the formed fibers tend not to fluff or produce lint due to surface friction, etc. In this sense, the fiber diameter of the nonwoven fabric layer (I layer) is preferably 0.1 to 3.8 μm, more preferably 0.2 to 3.0 μm, and further preferably 0.3 to 2.5 μm. The fiber diameter described in this specification can be evaluated by measuring the fiber diameter using a microscope.
[0041] The nonwoven fabric layer (II layer) is composed of thermoplastic resin fibers having a fiber diameter of 4.0 μm or more and 30.0 μm or less. When the fiber diameter is 30.0 μm or less, the fiber diameter is not too large and tends not to inhibit ion permeability. The nonwoven fabric layer (II layer) may contain fibers other than thermoplastic resin fibers having a fiber diameter of 4.0 μm or more and 30.0 μm or less within a range that does not impair the effects of the present invention, but typically consists only of thermoplastic resin fibers having a fiber diameter of 4.0 μm or more and 30.0 μm or less. Just as the fiber diameter in the above-mentioned I layer is important, the fiber diameter in the II layer is also important. If the fiber diameter of the fiber constituting the II layer is 30.0 μm or less, the surface smoothness is high, and when the I layer and the II layer are laminated so as to be in contact with each other, the fibers constituting the I layer can be more uniformly layered without unevenness in the fiber weight between the fibers constituting the II layer. This allows the fibers to be distributed more uniformly in the laminated nonwoven fabric. As a result, it is possible to improve the interface bonding. On the other hand, when the fiber diameter of the fiber constituting the second layer is 4.0 μm or more, the laminated nonwoven fabric has sufficient strength and tends to have stable mechanical strength. In this sense, the fiber diameter of the fiber constituting the second layer is preferably 4.0 to 28 μm, more preferably 5.0 to 25 μm, and even more preferably 6.0 to 20 μm.
[0042] In the electrolyte laminate of the present invention, an ultrafine fiber nonwoven fabric layer (I layer) can be provided inside or on the surface of the nonwoven fabric. In the I layer, the fiber diameter is small, so the fiber gaps are small, the fibers are uniformly distributed, and the specific surface area is large. By having this fiber layer I, a separator with excellent electrical insulation between electrodes can be produced, as it exhibits high barrier properties due to its dense structure. In addition, the large specific surface area of the ultrafine fibers provides excellent electrolyte retention and excellent ion permeability.
[0043] In the present invention, by disposing the ultrafine fiber nonwoven fabric layer (I layer) adjacent to the II layer, the integrity of the electrolyte and the laminated nonwoven fabric can be increased, and the interface bonding can be improved.
[0044] In the present invention, a nonwoven fabric layer (II layer) made of thermoplastic resin fibers can be provided as a support layer reinforcing the nonwoven fabric layer (I layer). In addition, the nonwoven fabric layer (I layer) has a relatively low air permeability, and there is a concern that the ion permeability may decrease. However, by combining the nonwoven fabric layer (I layer) with a fiber layer (II layer) having a relatively large fiber diameter, the air permeability of the laminated nonwoven fabric can be improved, and an electrolyte laminate with excellent ion permeability can be obtained. Furthermore, in each production process of the electrolyte laminate and the battery or capacitor, the nonwoven fabric layer (II layer) protects the nonwoven fabric layer (I layer) from deformation and damage due to poor mechanical strength, so that the defective rate can be reduced and stable production can be achieved.
[0045] In the laminated nonwoven fabric, the I layer is essential for forming a dense structure, and the II layer is essential for making the laminated nonwoven fabric more stable (i.e., improving the tensile strength, bending strength, and surface abrasion resistance of the nonwoven fabric) and for stably maintaining the I layer in each process. For these reasons, the laminated nonwoven fabric having the I layer and the II layer is advantageous for producing a battery or a capacitor with good performance.
[0046] In the present invention, in order to produce a better, high-performance electrolyte laminate, a laminated nonwoven fabric consisting of three layers is more preferable.
[0047] In the present invention, the thermoplastic resin fiber in the nonwoven fabric layer (I layer and / or II layer) is preferably a thermoplastic synthetic long fiber. In this specification, the thermoplastic synthetic long fiber refers to a continuous long fiber made of a thermoplastic synthetic resin (polyalkylene terephthalate resin (PET, PBT, PTT, etc.) and its derivatives, polyolefin resin (PE, PP, etc.) and its derivatives, polyamide resin such as N6, N66, N612 and its derivatives; polyoxymethylene ether resin (POM, etc.), PEN, PPS, PPO, polyketone resin, polyketone resin such as PEEK, thermoplastic polyimide resin such as TPI, or a copolymer mainly made of these resins or a mixture thereof). Here, the continuous long fiber refers to a fiber as defined by JIS-L0222. A nonwoven fabric made of thermoplastic synthetic long fiber can have sufficient mechanical strength. In addition, a nonwoven fabric made of thermoplastic synthetic long fiber is less likely to generate lint when slitting and when subjected to external friction, and is also resistant to abrasion. Examples of thermoplastic synthetic long fibers include long fibers made of crystalline resins, which will be listed later. On the other hand, when short fibers are used as thermoplastic resin fibers, the crystalline resin can be mixed with a thermoplastic resin having a lower melting point than the crystalline resin. The mixture may be a fiber made of a single resin, or a single fiber may contain two or more resins with different melting points. For example, a sheath-core yarn made of a core and a sheath, in which the melting point of the thermoplastic resin in the sheath is lower than that of the thermoplastic resin in the core, can be used. For example, a sheath-core yarn made of a PET core and a PET copolymerized sheath can be used.
[0048] <1-2. Ion-transporting organic substances> The ion transporting organic material in this embodiment includes at least one salt and an ion dissociation promoter, or includes at least one single ion conducting polymer.
[0049] The consistency of the ion transporting organic material at 25°C is preferably 100 or more and less than 400. With a consistency in this range, the first solid electrolyte layer and the second solid electrolyte layer used in the present invention can transmit the fluidity for forming an interface with the electrodes in contact with each other and the external pressure for forming the interface to the interface bonding, and the interface between the electrode and the ion transporting organic material is bonded well. From this viewpoint, the consistency of the ion transporting organic material at 25°C is preferably within the range of 110 to 380, 120 to 360, or 130 to 350.
[0050] The consistency is measured using a consistency tester as specified in the "Consistency Test Method" of JIS K 2220 (Grease), the sample is packed into a specified grease cup so that the surface is flat, and after keeping the temperature at 22±0.5°C, a cone is inserted vertically for 5 seconds. The consistency of the sample is expressed as a value obtained by measuring the penetration depth to the nearest 0.1 mm and multiplying this by 10.
[0051] From the viewpoint of enhancing the interface forming ability, the ion transporting organic material preferably contains a nitrile group, and more preferably contains a nitrile group derived from an ion dissociation promoter described below.
[0052] <1-3. Salt> The salt contained in the ion conductor in this embodiment may be any salt that is used in the electrolyte of a non-aqueous secondary battery.
[0053] The salt content in the ionic conductor of this embodiment is not particularly limited, but is preferably 0.2 mol or more per 1 L of non-aqueous solvent, more preferably 0.5 mol or more, and even more preferably 0.8 mol or more. The salt content is preferably 15 mol or less per 1 L of non-aqueous solvent, more preferably 4 mol or less, and even more preferably 2.8 mol or less. When the salt content is within the above range, the ionic conductivity tends to increase and high output characteristics can be expressed, and the storage characteristics and other battery characteristics tend to be further improved while maintaining the excellent performance of the ionic conductor.
[0054] The salt is not particularly limited as long as it is a salt used as a normal non-aqueous electrolyte, and any salt may be used. Specific examples of such lithium salts include LiPF6, LiBF4, LiClO4, LiAsF6, Li2SiF6, LiSbF6, LiAlO4, LiAlCl4, Li2B 10 H 10-a X a [In the formula, X is selected from F, Cl, Br, or I, and a is an integer of 0 to 10], LiB 12 H 12-b Y b [In the formula, Y is selected from F, Cl, Br, or I, and b is an integer of 0 to 12], 11 H 12-c Z c Lithium salt represented by the formula LiCBH, wherein Z is selected from F, Cl, Br, or I, and c is an integer of 0 to 12. 10-d W d Lithium salts represented by the formula (wherein X is selected from F, Cl, Br, or I, and d is an integer of 0 to 10); LiN(SO2C) such as LiN(SO2F)2, LiN(SO2CF3)2, and LiN(SO2C2F5)2; m F 2m+1 Lithium salts represented by the formula (wherein m is an integer of 1 to 8); LiPF such as LiPF5(CF3) n (C p F 2p+1 ) 6-n [wherein n is an integer of 1 to 5, and p is an integer of 1 to 8]; LiBF such as LiBF3(CF3) q (C s F 2s+1 ) 4-q[wherein q is an integer of 1 to 3, and s is an integer of 1 to 8]; lithium bis(oxalato)borate (LiBOB) represented by LiB(C2O4)2; lithium salts of borates having halogenated organic acids as ligands; lithium oxalatodifluoroborate (LiODFB) represented by LiBF2(C2O4); lithium bis(malonate)borate (LiBMB) represented by LiB(C3O4H2)2; lithium salts such as lithium tetrafluorooxalatophosphate represented by LiPF4(C2O4); and lithium salts represented by the following general formulas (1a), (1b), and (1c): LiC(SO2R 2 )(SO 2 R 3 )(SO2R 4 ) (1a) LiN(SO2OR 5 )(SO2OR 6 ) (1b) LiN(SO2R 7 )(SO2OR 8 ) (1c) {where, R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , and R 8 may be the same or different and represent a perfluoroalkyl group having 1 to 8 carbon atoms.}. Among them, the salt contained in the ion conductor is preferably Li2B 10 H 10-a X a [In the formula, X is selected from F, Cl, Br, or I, and a is an integer of 0 to 10], LiB 12 H 12-b Y b [In the formula, Y is selected from F, Cl, Br, or I, and b is an integer of 0 to 12], 11 H 12-c Z c Lithium salt represented by the formula LiCBH, wherein Z is selected from F, Cl, Br, or I, and c is an integer of 0 to 12. 10-d Wd In the formula, X is selected from F, Cl, Br, or I, and d is an integer of 0 to 10; LiN(SO2F)2, LiN(SO2CF3)2, and LiN(SO2C2F5)2 are preferred, and Li2B 10 H 10-a X a [In the formula, X is selected from F, Cl, Br, or I, and a is an integer of 0 to 10], LiB 12 H 12-b Y b [In the formula, Y is selected from F, Cl, Br, or I, and b is an integer of 0 to 12], 11 H 12-c Z c Lithium salt represented by the formula LiCBH, wherein Z is selected from F, Cl, Br, or I, and c is an integer of 0 to 12. 10-d W d It is preferable that the lithium salt contained is represented by the following formula: (wherein X is selected from F, Cl, Br, or I, and d is an integer of 0 to 10). The lithium salt may be used alone or in combination of two or more kinds.
[0055] <1-4. Ion dissociation promoter> In this embodiment, the ion dissociation promoter refers to a molecule and a polymer for stabilizing a cation dissociated from a salt. The origin of the term is that, for example, in the case of a lithium ion battery, a carbonate-based material is generally mixed to stabilize the lithium ion as a cation, and it is helpful to understand that the ion dissociation promoter is equivalent to this carbonate-based material.
[0056] It is preferable that the ion dissociation promoter has poor fluidity at room temperature. Poor fluidity specifically means that the viscosity is 10 mPa·s or more. This reduces the fluidity of the ion dissociation promoter, which is different from that of general lithium-ion batteries, and is expected to improve safety.
[0057] Examples of the ion dissociation promoter in this embodiment include polyalkylene oxides: polyethylene oxide; polyethylene carbonate-based materials; cyano group-containing hydrogenated nitrile rubber-based materials, hydrogenated nitrile butadiene rubber (HNBR); carborane-based materials: ortho-carborane, meta-carborane, para-carborane; adamantane-based materials: 2-adamantanone, 1-adamantanone, 1-adamantanecarbonitrile, 2-adamantanecarbonitrile; dinitrile compounds: succinonitrile, methylsuccinonitrile, tetramethylsuccinonitrile. Examples of the ion dissociation promoter include, but are not limited to, tolyl, azobisisobutyronitrile, glutaronitrile, adiponitrile, pimelonitrile, octanedinitrile, azelanitrile, and sebaconitrile; cyano group-containing polyoxetane described in JP-A-2008-277218; cyano group-containing polyvinyl alcohol described in JP-A-2006-307012; and copolymers of a plurality of monomers constituting these polymers, PIM: a polymer consisting of the following repeating unit (A) {wherein n is a number exceeding 1, for example, an integer of 10 to 10,000}. From the viewpoint of enhancing the interface forming ability, the ion dissociation promoter preferably contains a nitrile group, and HNBR, 1-adamantanecarbonitrile, 2-adamantanecarbonitrile, a dinitrile compound, cyano group-containing polyoxetane, cyano group-containing polyvinyl alcohol, and PIM are preferred. [ka]
[0058] The above solvent molecules can be produced by known synthesis methods, synthesis methods as required, and the like.
[0059] <1-5. Single-ion conductive polymer> The single ion conductive polymer of the present embodiment refers to an anionic polymer lithium salt having an ionically dissociable group. Examples of the ionically dissociable group include a carboxylate group, a sulfonate group, a sulfonimide group, and a phenolate group. The main chain skeleton may be, for example, a polyethylene skeleton, but the structure is not limited depending on the flexibility of the polymer.
[0060] <1-6.Non-aqueous solvents> The ion transporting organic material of the present embodiment may consist of only the above-mentioned solvent molecule and solvent polymer, and also a salt, or may contain a non-aqueous solvent in addition to these.
[0061] The non-aqueous solvent in this embodiment is not particularly limited as long as it does not impede the solution of the problems by the present invention. The non-aqueous solvent is preferably a substance that contributes to improving the performance of the ion-transporting organic material and the non-aqueous secondary battery of this embodiment. The non-aqueous solvent may be used alone or in combination of two or more components.
[0062] The other non-aqueous solvent to be added to the ion transporting organic material of the present embodiment is not particularly limited, and examples thereof include aprotic solvents, and aprotic polar solvents are preferred.
[0063] Specific examples of such non-aqueous solvents include cyclic carbonates such as ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, trans-2,3-butylene carbonate, cis-2,3-butylene carbonate, 1,2-pentylene carbonate, trans-2,3-pentylene carbonate, cis-2,3-pentylene carbonate, trifluoromethylethylene carbonate, fluoroethylene carbonate, and 1,2-difluoroethylene carbonate; lactones such as γ-butyrolactone and γ-valerolactone; sulfur compounds such as sulfolane and dimethylsulfoxide; cyclic ethers such as tetrahydrofuran, 1,4-dioxane, and 1,3-dioxane; methyl ethyl carbonate, Examples of the nitriles include linear carbonates such as dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, methyl butyl carbonate, dibutyl carbonate, ethyl propyl carbonate, and methyl trifluoroethyl carbonate; mononitriles such as propionitrile, butyronitrile, valeronitrile, benzonitrile, and acrylonitrile (excluding acetonitrile); alkoxy-substituted nitriles such as methoxyacetonitrile and 3-methoxypropionitrile; linear carboxylic acid esters such as methyl propionate; linear ethers such as dimethoxyethane, and halides such as fluorinated products thereof. These may be used alone or in combination of two or more.
[0064] The content of the non-aqueous solvent in the ion-transporting organic material of the present embodiment is not particularly limited, but is 0 to 40% by mass based on the total amount of the ion-transporting organic material of the present embodiment. The lower limit is preferably 0.1% by mass or more, and more preferably 0.5% by mass or more. The upper limit is more preferably 30% by mass, and more preferably 25% by mass or less.
[0065] <1-7. Additives> The ion-transporting organic material of the present embodiment may consist only of the above-mentioned solvent molecules and salts, or may consist only of the above-mentioned solvent molecules, the above-mentioned salts and a non-aqueous solvent, or may contain additives other than these.
[0066] The additive in this embodiment is not particularly limited as long as it does not impede the solution of the problems by the present invention, and may substantially overlap with the substance that plays the role of a solvent that dissolves or solidifies lithium salts (i.e., the above-mentioned non-aqueous solvent). The additive is preferably a substance that contributes to improving the performance of the ion-transporting organic material and the non-aqueous secondary battery in this embodiment. However, the additive also includes a substance that is not directly involved in the electrochemical reaction. The additive may be used alone or in combination of two or more components.
[0067] The additives may include, for example, additives that protect the electrodes.
[0068] Specific examples of the additive include 4-fluoro-1,3-dioxolane-2-one, 4,4-difluoro-1,3-dioxolane-2-one, cis-4,5-difluoro-1,3-dioxolane-2-one, trans-4,5-difluoro-1,3-dioxolane-2-one, 4,4,5-trifluoro-1,3-dioxolane-2-one, 4,4,5,5-tetrafluoro-1,3-dioxolane-2-one, and 4,4,5-trifluoro-5 Fluoroethylene carbonates, such as 4-methyl-1,3-dioxolan-2-one; unsaturated bond-containing cyclic carbonates, such as vinylene carbonate, 4,5-dimethylvinylene carbonate, and vinylethylene carbonate; lactones, such as γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ-caprolactone, and ε-caprolactone; cyclic ethers, such as 1,2-dioxane;
[0069] Methyl formate, methyl acetate, methyl propionate, methyl butyrate, ethyl formate, ethyl acetate, ethyl propionate, ethyl butyrate, n-propyl formate, n-propyl acetate, n-propyl propionate, n-propyl butyrate, isopropyl formate, isopropyl acetate, isopropyl propionate, isopropyl butyrate, n-butyl formate, n-butyl acetate, n-butyl propionate, n-butyl butyrate, isobutyl formate, isobutyl acetate, isobutyl propionate, isopropyl carboxylic acid esters represented by isobutyl butyrate, sec-butyl formate, sec-butyl acetate, sec-butyl propionate, sec-butyl butyrate, tert-butyl formate, tert-butyl acetate, tert-butyl propionate, tert-butyl butyrate, methyl pivalate, n-butyl pivalate, n-hexyl pivalate, n-octyl pivalate, dimethyl oxalate, ethyl methyl oxalate, diethyl oxalate, diphenyl oxalate, malonic acid esters, fumaric acid esters, and maleic acid esters;
[0070] Examples of the sulfur compounds include amides such as N-methylformamide, N,N-dimethylformamide, and N,N-dimethylacetamide; cyclic sulfur compounds such as ethylene sulfite, propylene sulfite, butylene sulfite, pentene sulfite, sulfolane, 3-methylsulfolane, 3-sulfolene, 1,3-propane sultone, 1,4-butane sultone, 1,3-propanediol sulfate, tetramethylene sulfoxide, and thiophene 1-oxide; aromatic compounds such as monofluorobenzene, biphenyl, and fluorinated biphenyl; nitro compounds such as nitromethane; Schiff bases; Schiff base complexes; and oxalate complexes. These compounds may be used alone or in combination of two or more.
[0071] The content of the additive in the ion transporting organic material of this embodiment is not particularly limited, but is preferably 0.1 to 30 mass %, and more preferably 0.1 to 10 mass %, based on the total amount of the ion transporting organic material of this embodiment.
[0072] In this embodiment, the higher the content of the additive, the more the deterioration of the ion-transporting organic material is suppressed, but the lower the content of the additive, the more the high-output characteristics of the non-aqueous secondary battery in a low-temperature environment are improved. Therefore, by adjusting the content of the additive within the above range, it is possible to maximize the excellent performance based on the high ion conductivity of the ion-transporting organic material without impairing the basic function of the non-aqueous secondary battery. By preparing the electrolyte solution with such a composition, it is possible to further improve the cycle performance, the high-output performance in a low-temperature environment, and all other battery characteristics of the non-aqueous secondary battery containing the ion-transporting organic material.
[0073] <1-8. Other additives> In this embodiment, the ion-transporting organic material may contain other additives for achieving various physical properties against battery production or aging deterioration, such as handling during production or storage properties, in addition to battery characteristics such as moldability or strength. Examples of additives other than the additives described in <1-6> above include non-ion conductive polymers (PVDF (polyvinylidene fluoride), PTFE (polytetrafluoroethylene), polycarboxylic acid, polysulfonic acid, polyacrylic acid, styrene butadiene rubber, fluororubber, etc.), non-ion conductive inorganic fillers (e.g., TiO2, SiO2, BaTiO3, Al2O3, boehmite, etc.), organic fibers (e.g., polyethylene, polypropylene, cellulose, etc.), etc.
[0074] The content of other additives in the ion transporting organic material of this embodiment is not particularly limited, but is preferably 0.1 to 30 mass %, and more preferably 0.1 to 10 mass %, based on the total amount of the ion transporting organic material of this embodiment.
[0075] <2. Second ion transporting substance> The ion transporting organic material of the present embodiment may be composed of only the above-mentioned solvent molecules and salts, may be composed of only the above-mentioned solvent molecules, the above-mentioned salts, and non-aqueous solvents, may be composed of only the above-mentioned solvent molecules, the above-mentioned salts, non-aqueous solvents, and additives, or may contain a second ion transporting material other than these. The second ion transporting material may be a combination of a known polymer-based solid electrolyte, an oxide-based solid electrolyte, or a sulfide-based solid electrolyte. There is no particular restriction on the content of the second ion transporting material in the ion transporting organic material of the present embodiment. When the characteristics of the ion transporting organic material of the present embodiment are good, the content of the second ion transporting material is preferably 0.1 to 30% by mass, more preferably 0.1 to 10% by mass. When the characteristics of the ion transporting material to be combined are good, the content of the ion transporting material of the present embodiment is preferably 0.1 to 30% by mass, more preferably 0.1 to 10% by mass.
[0076] <3. Method for producing ion-transporting organic material> The method for producing the ion-transporting organic material of the present invention is not limited by the present invention, and a mixing and molding process by a known wet or dry method may be used. For example, when an ion conductor is produced by a wet method, a solvent molecule and a lithium salt are dissolved in a solvent, and a film is formed by a method such as doctor blade, die coating, comma coating, screen printing, etc. At this time, the concentration of the solution or the number of coatings can be adjusted to adjust the thickness of the coating film that is finally coated. The drying process is a process for removing the solvent and moisture in the ion-transporting organic material coating film coated on the support, and varies depending on the solvent used. As an example, it is performed in a vacuum oven at 50 to 200 ° C. Examples of drying methods include drying with warm air, hot air, low humidity air, vacuum drying, and drying by irradiation with (far) infrared rays or electron beams. The drying time is not particularly limited, but is usually performed within a range of 30 seconds to 24 hours.
[0077] When preparing an ion-transporting organic material by a dry method, it can be produced by extruding a composition containing suitable components in suitable ratios. Using a single-screw extruder or a twin-screw extruder, the solvent molecules can be melted, the salt can be added, kneaded, and then extruded. It is preferable to produce it using a twin-screw extruder, which allows for better dispersion.
[0078] The timing of addition of the additives in <1-6>, the other additives in <1-7>, the non-aqueous solvent, and the second ion-transporting substance can be appropriately adjusted in consideration of their productivity, storage properties, and the like.
[0079] <4. Method for producing electrolyte laminate> An example of the method for producing the electrolyte laminate according to the present embodiment includes, for example, (i) a step of simultaneously forming the first, second, and third electrolyte layers containing an electrolyte; and / or (ii) a step of forming the first and third electrolyte layers on the second electrolyte layer including the electrolyte and a support. The method for producing the electrolyte laminate is not limited to the steps (i) and (ii), and a known method for producing an electrolyte laminate in which the first, second, and third electrolyte layers can be bonded and laminated in this order using a base material, an electrolyte, and an ionic organic material, or a known solid electrolyte laminate can be used.
[0080] <5. Positive electrode and positive electrode current collector> The positive electrode is not particularly limited as long as it functions as a positive electrode for a non-aqueous secondary battery, and may be a known positive electrode. A preferred positive electrode in this embodiment contains a positive electrode active material, and optionally further contains a conductive assistant, a binder, and an ion conductor.
[0081] It is preferable that the positive electrode contains one or more materials selected from the group consisting of materials capable of absorbing and releasing ions as a positive electrode active material, since this tends to enable a high voltage and a high energy density to be obtained. Examples of such materials include those represented by the following general formulas (2a) and (2b): Li x MO2(2a) Li y M2O4(2b) {wherein M represents one or more metals selected from transition metals, x represents a number from 0 to 1, and y represents a number from 0 to 2}, as well as other lithium-containing compounds.
[0082] Examples of the lithium-containing compounds represented by the general formulas (2a) and (2b) include lithium cobalt oxides such as LiCoO2; lithium manganese oxides such as LiMnO2, LiMn2O4, and Li2Mn2O4; lithium nickel oxides such as LiNiO2; z Examples of the lithium-containing composite metal oxide include a lithium-containing composite metal oxide represented by MO2 (wherein M represents one or more elements selected from the group consisting of Ni, Mn, Co, Al, and Mg, and z represents a number greater than 0.9 and less than 1.2).
[0083] The other lithium-containing compounds may be any compounds containing lithium. Examples of such other lithium-containing compounds include composite oxides containing lithium and a transition metal element, metal chalcogenides containing lithium, phosphate compounds containing lithium and a transition metal element, and metal silicate compounds containing lithium and a transition metal element (e.g., Li t M u SiO4, M is the same as in the above formula (2a), t is a number from 0 to 1, and u is a number from 0 to 2.) In terms of obtaining a higher voltage, the other lithium-containing compounds are particularly preferably a composite oxide containing lithium and one or more transition metal elements selected from the group consisting of cobalt (Co), nickel (Ni), manganese (Mn), iron (Fe), copper (Cu), zinc (Zn), chromium (Cr), vanadium (V), and titanium (Ti), and a phosphate compound.
[0084] More specifically, the other lithium compounds are preferably a composite oxide containing lithium and a transition metal element, a metal chalcogenide containing lithium and a transition metal element, and a metal phosphate compound containing lithium, and more preferably a composite oxide containing lithium and a transition metal element and a metal phosphate compound containing lithium. For example, the compounds represented by the following general formulas (3a) and (3b) are respectively: Li v M I O2(3a) Li w M II PO4(3b) {In formula, M I and M II each represents one or more transition metal elements, the values of v and w vary depending on the charge / discharge state of the battery, v represents a number from 0.05 to 1.10, and w represents a number from 0.05 to 1.10.
[0085] The compound represented by the general formula (3a) has a layered structure, and the compound represented by the general formula (3b) has an olivine structure. For the purpose of stabilizing the structure, these compounds may be compounds in which a part of the transition metal element is replaced by Al, Mg, or other transition metal element, compounds in which these metal elements are contained in the crystal grain boundaries, compounds in which a part of the oxygen atoms is replaced by fluorine atoms, or compounds in which at least a part of the surface of the positive electrode active material is coated with another positive electrode active material.
[0086] As the positive electrode active material in this embodiment, only the lithium-containing compound as described above may be used, or the lithium-containing compound may be used in combination with other positive electrode active materials.
[0087] Examples of such other positive electrode active materials include metal oxides or metal chalcogenides having a tunnel structure and a layer structure, sulfur, conductive polymers, etc. Examples of metal oxides or metal chalcogenides having a tunnel structure and a layer structure include MnO2, FeO2, FeS2, V2O5, and V6O 13Examples of the oxides include oxides, sulfides, and selenides of metals other than lithium, such as TiO2, TiS2, MoS2, and NbSe2.
[0088] Examples of the conductive polymer include conductive polymers typified by polyaniline, polythiophene, polyacetylene, and polypyrrole. The positive electrode active material may be used alone or in combination of two or more.
[0089] When a lithium-containing compound and another positive electrode active material are used in combination as the positive electrode active material, the ratio of the two is preferably 80 mass % or more, and more preferably 85 mass % or more, of the lithium-containing compound relative to the total positive electrode active material.
[0090] The number average particle diameter (primary particle diameter) of the positive electrode active material is preferably 0.05 μm to 100 μm, more preferably 1 μm to 10 μm. The number average particle diameter of the positive electrode active material can be measured by a wet particle diameter measuring device (for example, a laser diffraction / scattering type particle size distribution meter, a dynamic light scattering type particle size distribution meter, etc.). Alternatively, it can be obtained by randomly extracting 100 particles from an image observed using a transmission electron microscope, analyzing them with image analysis software (for example, image analysis software manufactured by Asahi Conditioning Engineering Co., Ltd., product name "A-zo-kun"), and calculating the arithmetic mean. In this case, if the number average particle diameter differs between measurement methods for the same sample, a calibration curve prepared for a standard sample may be used.
[0091] Examples of the conductive assistant include carbon black, such as graphite, acetylene black, and ketjen black, and carbon fiber. The number average particle size (primary particle size) of the conductive assistant is preferably 10 nm to 10 μm, and more preferably 20 nm to 1 μm. The number average particle size of the conductive assistant is measured in the same manner as the number average particle size of the positive electrode active material. The content of the conductive assistant is preferably 10 parts by mass or less, and more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the positive electrode active material.
[0092] Examples of the binder include PVDF, PTFE, polyacrylic acid, styrene-butadiene rubber, and fluororubber. The content of the binder is preferably 6 parts by mass or less, and more preferably 0.5 to 4 parts by mass, per 100 parts by mass of the positive electrode active material.
[0093] The content of the ion transporting organic material is preferably 25 parts by mass or less, and more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the positive electrode active material.
[0094] The positive electrode is obtained, for example, as follows. That is, first, a conductive assistant, a binder, a lithium ion conductor, etc. are added to the positive electrode active material as necessary, and the positive electrode mixture is dispersed in a solvent to prepare a positive electrode mixture-containing slurry. The solvent is not particularly limited, and a conventionally known solvent may be used, for example, N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, water, etc. Here, the solid content concentration in the positive electrode mixture-containing slurry is preferably 30 to 80 mass%, more preferably 40 to 70 mass%. Next, the positive electrode mixture-containing slurry is applied onto a positive electrode current collector and dried to form a positive electrode active material layer.
[0095] The positive electrode current collector is made of a metal foil such as aluminum foil, nickel foil, stainless steel foil, etc. The positive electrode current collector may have a carbon coating on the surface, or may be processed into a mesh shape. The thickness of the positive electrode current collector is preferably 5 to 40 μm, more preferably 7 to 35 μm, and further preferably 9 to 30 μm.
[0096] The positive electrode active material layer obtained after drying is compressed by a roll press or the like to form a positive electrode mixture layer (positive electrode). The thickness of the compressed positive electrode mixture is preferably 10 to 300 μm, more preferably 20 to 280 μm, and further preferably 30 to 250 μm.
[0097] <6. Negative electrode and negative electrode current collector> The negative electrode is not particularly limited as long as it functions as a negative electrode of a non-aqueous secondary battery, and may be a known negative electrode. A preferred negative electrode in this embodiment contains a negative electrode active material, and optionally further contains a conductive assistant, a binder, and an ion-transporting organic material.
[0098] The negative electrode preferably contains one or more materials selected from the group consisting of materials capable of absorbing and releasing lithium ions as the negative electrode active material, and metallic lithium. Examples of such materials include metallic lithium, amorphous carbon (hard carbon), artificial graphite, natural graphite, pyrolytic carbon, coke, glassy carbon, a sintered body of an organic polymer compound, a carbon material represented by mesocarbon microbeads, carbon fiber, activated carbon, graphite, carbon colloid, and carbon black; and a material containing an element capable of forming an alloy with lithium. Examples of the coke include pitch coke, needle coke, and petroleum coke. The sintered body of an organic polymer compound is a material obtained by sintering a polymer material such as a phenol resin or a furan resin at an appropriate temperature to carbonize it. The carbon material may contain, in addition to carbon, a different element or a different compound such as O, B, P, N, S, Si, SiC, SiO, SiO2, and B4C. The content of the different element or compound is preferably 0 to 10% by mass.
[0099] The material containing an element capable of forming an alloy with lithium may be a simple metal or semimetal element, an alloy, or a compound, and may have one or more of these phases at least in part.
[0100] In this specification, the term "alloy" includes not only those consisting of two or more metallic elements, but also those having one or more metallic elements and one or more metalloid elements. In addition, the alloy may contain nonmetallic elements as long as it has metallic properties as a whole. The structure of the alloy may be a solid solution, a eutectic (eutectic mixture), or an intermetallic compound, or two or more of these may coexist.
[0101] Examples of metal elements and metalloid elements that can form an alloy with lithium include titanium (Ti), tin (Sn), lead (Pb), aluminum (Al), indium (In), silicon (Si), zinc (Zn), antimony (Sb), bismuth (Bi), gallium (Ga), germanium (Ge), arsenic (As), silver (Ag), hafnium (Hf), zirconium (Zr), and yttrium (Y). Among these, metal elements and metalloid elements in Group 4 or Group 14 of the long periodic table are preferred. Particularly preferred are titanium, silicon, and tin, which have a high ability to absorb and release lithium and can obtain a high energy density.
[0102] Examples of tin alloys include those having, as a second constituent element other than tin, one or more elements selected from the group consisting of silicon, magnesium (Mg), nickel, copper, iron, cobalt, manganese, zinc, indium, silver, titanium (Ti), germanium, bismuth, antimony, and chromium (Cr).
[0103] Examples of silicon alloys include those having, as a second constituent element other than silicon, one or more elements selected from the group consisting of magnesium, nickel, copper, iron, cobalt, manganese, zinc, indium, silver, titanium, germanium, bismuth, antimony, and chromium.
[0104] Examples of the titanium compound, tin compound, and silicon compound include those containing oxygen (O) or carbon (C). In this case, in addition to titanium, tin, or silicon, the compound may contain the above-mentioned second constituent element.
[0105] The negative electrode is a negative electrode active material, 0.4 to 3 V vs. Li / Li + The lithium ion-absorbing material may contain a metal compound capable of absorbing lithium ions within the above range. Examples of such metal compounds include metal oxides, metal sulfides, and metal nitrides.
[0106] Examples of metal oxides include titanium oxide, lithium titanium oxide (lithium titanium-containing composite oxide), tungsten oxide (e.g., WO3), and amorphous tin oxide (e.g., SnB 0.4 P 0.6 O 3.1 ), tin silicon oxide (e.g., SnSiO3), and silicon oxide (SiO). Among these, titanium oxide and lithium titanium oxide are preferred.
[0107] Examples of lithium titanium oxide include lithium titanate having a spinel structure {e.g., Li4+aTi5O 12 (wherein a can vary within the range of -1≦a≦3 due to charge and discharge reactions)}, lithium titanate with a ramsdellite structure {for example, Li2+bTi3O7 (wherein b can vary within the range of -1≦b≦3 due to charge and discharge reactions)}, and the like.
[0108] As the titanium oxide, either one containing Li before charging and discharging or one not containing Li can be used. As the titanium oxide not containing Li before charging and discharging (at the time of synthesis), for example, titanium oxide (e.g., TiO2, H2Ti 12 O 25 ), titanium composite oxides containing Ti and at least one element selected from the group consisting of P, V, Sn, Cu, Ni, and Fe. TiO2 is preferably anatase type with low crystallinity and heat treatment temperature of 300 to 500°C. Examples of titanium composite oxides include TiO2-P2O5, TiO2-V2O5, TiO2-P2O5-SnO2, and TiO2-P2O5-MeO (wherein Me is at least one element selected from the group consisting of Cu, Ni, and Fe). The titanium composite oxide preferably has a microstructure with low crystallinity in which a crystalline phase and an amorphous phase coexist, or in which an amorphous phase exists alone. By having such a microstructure, the cycle performance of a non-aqueous secondary battery can be significantly improved.
[0109] Examples of titanium oxides that contain Li before charge and discharge (at the time of synthesis) include Li cExamples include TiO2 (where 0 < c ≤ 1.1).
[0110] Examples of metal sulfides include titanium sulfide (e.g., TiS2), molybdenum sulfide (e.g., MoS2), and iron sulfide (e.g., FeS, FeS2, Li g FeS2 (where g is 0 ≤ g ≤ 1)). Examples of metal nitrides include lithium cobalt nitride (e.g., Li d Co e N, 0 < d < 4, 0 < e < 0.5).
[0111] From the perspective of increasing the battery voltage, the negative electrode of the non-aqueous secondary battery in this embodiment preferably contains, as a negative electrode active material, a material that occludes lithium ions at a potential lower than 0.4V vs. Li / Li + Examples of such materials include carbon materials typified by amorphous carbon (hard carbon), artificial graphite, natural graphite, graphite, pyrolytic carbon, coke, glassy carbon, fired bodies of organic polymer compounds, mesocarbon microbeads, carbon fibers, activated carbon, graphite, carbon colloids, and carbon black. In addition, metal lithium, metal oxides, metal nitrides, lithium alloys, tin alloys, silicon alloys, intermetallic compounds, organic compounds, inorganic compounds, metal complexes, organic polymer compounds, etc. can be mentioned.
[0112] The negative electrode active material is used alone or in combination of two or more kinds.
[0113] The number average particle diameter (primary particle diameter) of the negative electrode active material is preferably 0.1 μm to 100 μm, more preferably 1 μm to 10 μm. The number average particle diameter of the negative electrode active material is measured in the same manner as that of the positive electrode active material.
[0114] Examples of the conductive assistant include carbon black, such as graphite, acetylene black, and ketjen black, and carbon fiber. The number average particle size (primary particle size) of the conductive assistant is preferably 10 nm to 10 μm, and more preferably 20 nm to 1 μm. The number average particle size of the conductive assistant is measured in the same manner as the number average particle size of the positive electrode active material. The content of the conductive assistant is preferably 20 parts by mass or less, and more preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of the negative electrode active material.
[0115] Examples of the binder include PVDF, PTFE, polyacrylic acid, styrene-butadiene rubber, and fluororubber. The content of the binder is preferably 10 parts by mass or less, and more preferably 0.5 to 6 parts by mass, relative to 100 parts by mass of the negative electrode active material.
[0116] The content of the ion transporting organic material is preferably 25 parts by mass or less, and more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the negative electrode active material.
[0117] The negative electrode is obtained, for example, as follows. That is, first, the negative electrode mixture obtained by adding a conductive assistant, a binder, a lithium ion conductor, etc. to the negative electrode active material as necessary and mixing the mixture is dispersed in a solvent to prepare a negative electrode mixture-containing slurry. There is no particular limitation on the solvent, and a conventionally known solvent may be used. For example, N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, water, etc. can be used. The solid content concentration in the negative electrode mixture-containing slurry is preferably 30 to 80 mass%, more preferably 40 to 70 mass%. Next, the negative electrode mixture-containing slurry is applied onto a negative electrode current collector and dried to form a negative electrode active material layer.
[0118] The negative electrode current collector is, for example, composed of a metal foil such as copper foil, nickel foil, stainless steel foil, etc. The negative electrode current collector may have a surface coated with carbon or may be processed into a mesh shape. The thickness of the negative electrode current collector is preferably 5 to 40 μm, more preferably 6 to 35 μm, and further preferably 7 to 30 μm.
[0119] The negative electrode active material layer obtained after drying is compressed by a roll press or the like to form a negative electrode mixture layer (negative electrode). The thickness of the negative electrode mixture after compression is preferably 10 to 300 μm, more preferably 20 to 280 μm, and further preferably 30 to 250 μm.
[0120] <7. Battery exterior> The structure of the battery exterior of the non-aqueous secondary battery in this embodiment is not particularly limited, and for example, either a battery can or a laminate film exterior can be used. For example, a metal can made of steel or aluminum can be used as the battery can. For example, a laminate film exterior can be used in which two laminate films made of a three-layer structure of heat-melting resin / metal film / resin are stacked with the heat-melting resin side facing inward and the ends are sealed by heat sealing.
[0121] When a laminate film exterior body is used, a positive electrode terminal (or a lead tab connected to the positive electrode terminal) and a negative electrode terminal (or a lead tab connected to the negative electrode terminal) may be connected to the positive electrode current collector and the negative electrode current collector, respectively, and the laminate film exterior body may be sealed with the ends of both terminals (or lead tabs) extended outside the exterior body.
[0122] <8. How to make a battery> The nonaqueous secondary battery of this embodiment is characterized by including the above-mentioned solid electrolyte laminate.
[0123] The nonaqueous secondary battery of this embodiment can be produced by a known method using, for example, the above-mentioned solid electrolyte laminate, positive electrode, and negative electrode.
[0124] First, a laminate consisting of a positive electrode, a negative electrode, and a solid electrolyte laminate is formed.
[0125] for example: A mode in which a positive electrode and a negative electrode are wound in a stacked state with a solid electrolyte laminate interposed therebetween to form a wound laminate; The laminate is folded or a plurality of the laminates are laminated to form a multi-layer laminate in which a solid electrolyte laminate and a separator are interposed between each of a plurality of pairs of positive electrodes and negative electrodes; etc. are possible.
[0126] Next, the above laminate is housed in a battery case (battery exterior) and sealed, thereby completing the nonaqueous secondary battery of this embodiment.
[0127] The shape of the nonaqueous secondary battery of this embodiment is not particularly limited, and for example, a cylindrical shape, an elliptical shape, a rectangular tube shape, a button shape, a coin shape, a flat shape, a laminate shape, and the like are suitably adopted.
[0128] The non-aqueous secondary battery of this embodiment can function as a battery by initial charging, but is stabilized by decomposing a part of the lithium ion conductor during initial charging. There is no particular restriction on the method of initial charging in this embodiment, but the initial charging is preferably performed at 0.001 to 0.3 C, more preferably at 0.002 to 0.25 C, and particularly preferably at 0.003 to 0.2 C. The initial charging can also be performed by passing through a constant voltage charge in the middle to give a favorable result. The constant current at which the rated capacity is discharged in one hour is 1 C. By setting the voltage range in which the lithium salt is involved in the electrochemical reaction to be long, a SEI (Solid Electrolyte Interface) is formed on the electrode surface, which has the effect of suppressing an increase in internal resistance including the positive electrode, and the reaction product is not firmly fixed only to the negative electrode, and in some way has a good effect on members other than the negative electrode, such as the positive electrode and the solid electrolyte laminate. For this reason, it is very effective to perform the initial charging while taking into consideration the electrochemical reaction of the lithium salt dissolved in the electrolyte.
[0129] The nonaqueous secondary battery of this embodiment can be used as a battery pack by connecting a plurality of batteries in series or in parallel. From the viewpoint of managing the charge / discharge state of the battery pack, the operating voltage range per battery is preferably 2 to 5 V, more preferably 2.5 to 5 V, and particularly preferably 2.75 V to 5 V. EXAMPLES
[0130] The present invention will now be illustrated by the following examples, which are not intended to limit the invention.
[0131] [Example 1] Lithium bis(trifluoromethane)sulfonimide (LiN(SOCF) hereinafter referred to as "LiTFSI"), cyano group-containing hydrogenated nitrile rubber (HNBR) consisting of the repeating unit (a) below, and polyethylene oxide (PEO) were dissolved in acetonitrile to prepare an ion-transporting organic material such that the LiTFSI salt concentration was 0.60 mol / L and the ratio of cyano groups in HNBR and acetonitrile was 3:7. [ka] {wherein x, y and z are each independently any number and can be determined according to the above ratio of cyano groups}
[0132] Separately, a laminated nonwoven fabric was prepared as a substrate by the following method. To obtain a microfiber web for the microfiber nonwoven fabric layer (I layer), a polyethylene terephthalate (PET) solution (using o-chlorophenol (OCP) as a solvent and having a solution viscosity of ηsp / c=0.50 measured at a temperature of 35°C) was used, and the spinning temperature was 300°C and heated air was 1000 Nm 3 The fibers were extruded toward a moving collection net under conditions of 1000 rpm / hr / m and spun by the meltblown method. At this time, the distance from the meltblown nozzle to the ultrafine fiber web was set to 100 mm, the suction force at the collection surface directly below the meltblown nozzle was set to 0.2 kPa, and the wind speed was set to 7 m / sec. The fiber diameter and crystallinity were adjusted by adjusting the amount of heated air. The obtained meltblown layer had an average fiber diameter of 1.6 μm and a basis weight of 2.0 g / m. 2 It was.
[0133] Next, to obtain a nonwoven fabric layer (II layer) composed of thermoplastic resin fibers, a general-purpose PET (as thermoplastic resin) solution (OCP was used as a solvent, and the solution viscosity measured at a temperature of 35°C was ηsp / c = 0.67) (the solution viscosity was measured with a viscosity tube in a thermostatic water bath at a temperature of 35°C. The same applies below.) was used, and filaments were spun at a spinning temperature of 300°C and a spinning speed of 4500 m / min by the spunbond method, and sprayed onto the ultrafine fiber web. Next, the fibers were charged with a corona charge of about 3 μC / g to fully open the filaments, and a laminated web consisting of a nonwoven fabric layer (I layer) composed of ultrafine fibers / a nonwoven fabric layer (II layer) composed of long thermoplastic resin fibers was obtained. The fiber diameter was adjusted by changing the pulling conditions. The spunbond layer had an average fiber diameter of 10 μm and a basis weight of 2.0 g / m 2 It was.
[0134] A nonwoven fabric layer (I layer) having an average fiber diameter of 1.6 μm and a basis weight of 2.0 g / m was formed on the laminated web obtained above in the same manner as in the formation of the ultrafine fiber web as the nonwoven fabric layer (I layer). 2 The laminated web was then heat-bonded with a flat roll heated to 120°C, and the thickness was adjusted with a calendar roll heated to 70°C. The thickness of the resulting laminated nonwoven fabric was 20 μm.
[0135] The laminated nonwoven fabric thus produced was coated with an ion-transporting organic material consisting of a LiTFSI:HNBR:PEO:acetonitrile mixture by die coating. A back roll was not provided, the substrate was arranged vertically, and the die head was pressed from the side. The mixture passed through the nonwoven fabric, and it was confirmed that a coating film was formed on the side opposite to the die-coated surface. By passing through a drying oven at 60 ° C., an electrolyte laminate was obtained in which the total thickness was 32 μm, the thickness of the substrate part of the laminated nonwoven fabric was 20 μm, and an electrolyte layer of 6 μm thickness was formed on both sides. When the composition of the electrolyte layer not including the substrate part in this electrolyte laminate was analyzed, the cyano group ratio of HNBR and acetonitrile was 3:5, and the LiTFSI salt concentration was 0.75 mol / L. On the other hand, it was found that the composition of the electrolyte in the substrate part was almost the same as the composition at the time of coating, and it was a laminate of different ion-transporting organic materials.
[0136] The cathode was a 40 μm composite membrane placed on a current collector made of aluminum coated with a carbon-based layer, the composite containing nickel-cobalt-manganese oxide cathode (Ni:Mn:Co=5:2:3) as the active material of the electrode, carbon black as the material causing electronic conductivity, and LiTFSI mixed in a ratio of 1.5 mol / L with HNBR and PEO as the ion-transporting organic material. The basis weight was 1.5 mA / cm. 2 The electrolyte laminate sandwiched between the cathode and anode was the one prepared above. The anode contained graphite:SiO = 95:5 (mass ratio), carbon nanotubes as a material for generating electronic conductivity, LiTFSI mixed at a ratio of 1.5 mol / L as an ion-transporting organic material, HNBR, and PEO. The density was 1.7 mA / cm 2 These were laminated and sealed with an aluminum laminate film exterior body. Then, they were pressed at 50°C and a pressure of 1 MPa for 100 seconds. This resulted in a battery including a cathode / (LiTFSI:HNBR:PEO:acetonitrile) / anode element.
[0137] [Example 2] In the same manner as in Example 1, LiTFSI, HNBR, and PEO were dissolved in acetonitrile to prepare an ion-transporting organic material so that the LiTFSI salt concentration was 0.60 mol / L and the cyano group ratio of HNBR to acetonitrile was 3:7. Short fiber PET with a fiber diameter of 10 μm and a length of 3 mm was added and kneaded, and the mixture was applied onto a release film with an applicator and then dried at 60°C to obtain an electrolyte film in which the short fiber PET support and the ion-transporting organic material were fused together. A LiTFSI:HNBR:PEO:acetonitrile mixture having the same composition was applied to the electrolyte film with an applicator and dried again at 60°C. A release-treated film was attached, and the back side of the electrolyte film was similarly coated and dried to obtain an electrolyte laminate. The thickness of each layer of the electrolyte laminate was 15 μm for the layer containing short fiber PET, 9 μm for both layers on both sides, and 33 μm in total. The drying time was adjusted so that the LiTFSI salt concentration of the electrolyte layer not containing short fiber PET was 0.75 mol / L. A battery was fabricated and evaluated in the same manner as in Example 1, except that the electrolyte laminate fabricated in Example 2 was used.
[0138] [Example 3] In the same manner as in Example 1, LiTFSI, HNBR and PEO were dissolved in acetonitrile to prepare an ion-transporting organic material so that the LiTFSI salt concentration was 0.60 mol / L and the cyano group ratio of the cyano group-containing hydrogenated nitrile rubber to acetonitrile was 3:7.
[0139] Separately, a nonwoven fabric was prepared as a substrate by the following method. To obtain a nonwoven layer (layer II) composed of thermoplastic resin fibers, a general-purpose PET (as thermoplastic resin) solution (OCP was used as a solvent, and the solution viscosity measured at a temperature of 35°C was ηsp / c = 0.67) was used, and filaments were spun at a spinning temperature of 300°C at a spinning speed of 4500 m / min by the spunbond method, and sprayed onto the ultrafine fiber web. The fibers were then charged with a corona charge of about 3 μC / g to fully open the filaments, yielding a nonwoven fabric composed of long thermoplastic resin fibers. The fiber diameter was adjusted by changing the traction conditions. The spunbond layer had an average fiber diameter of 10 μm and a basis weight of 6.0 g / m. 2 The nonwoven fabric layer (II layer) thus obtained was laminated with two nonwoven fabric layers (I layer) similar to those in Example 1, and thermally bonded with a flat roll heated to 120° C., and then the thickness was adjusted with a calendar roll heated to 70° C. The thickness of the laminated nonwoven fabric obtained was 20 μm.
[0140] The same ion-transporting organic material as in Example 1 was applied to the laminated nonwoven fabric produced by die coating in the same manner as in Example 1, to obtain an electrolyte laminate having a total thickness of 32 μm, a thickness of 20 μm of the substrate of the laminated nonwoven fabric, and an electrolyte layer having a thickness of 6 μm formed on both sides thereof. When the composition of the electrolyte layer not including the substrate in this electrolyte laminate was analyzed, the cyano group ratio of HNBR and acetonitrile was 3:5, and the LiTFSI salt concentration was 0.75 mol / L. On the other hand, the composition of the electrolyte in the substrate was almost the same as that at the time of coating, and it was found to be a laminate of different ion-transporting organic materials. The battery was produced and evaluated in the same manner as in Example 1, except that the electrolyte laminate produced in Example 3 was used.
[0141] [Rate test, cycle test, impedance measurement] The conditioning conditions for the obtained battery were as follows: The battery was restrained at a pressure of 1 MPa, and charging was performed by CCCV charging at 0.1 C. The CV time was set to 1 hour, and the end voltage was set to 4.2 V. Discharging was performed by CC discharging at 0.1 C. The end voltage was set to 3.0 V. Thereafter, in order to calculate the discharge capacity, the capacity was confirmed under the following conditions: Charging was performed by CCCV charging at 0.1 C. The CV time was set to 1 hour, and the end voltage was set to 4.2 V. Discharging was performed by CC discharging at 0.1 C. The end voltage was set to 3.0 V.
[0142] The conditions for the rate test were as follows: For the cells for which conditioning and discharge capacity had been confirmed, the current value was changed to 2C, and the same voltage control and termination conditions were used as in confirming the discharge capacity.
[0143] The cycle test conditions were as follows. The cells for which the discharge capacity had been confirmed were reset to each confining pressure condition, and charging was performed by CCCV charging at 1C. The CV time was 1 hour, and the end voltage was set to 4.2V. Discharging was performed by CC discharging at 1C. The end voltage was set to 3.0V. The discharge capacity retention rate in the cycle test was calculated based on the first 1C discharge capacity.
[0144] Impedance measurements were performed as follows. Comparing Example 1 to Example 3, Example 1 did not show any cycle deterioration at any confining pressure, and even after 200 cycles, it showed a discharge capacity retention rate of 80% or more, whereas in Example 2 and Example 3, the discharge capacity fell below 80% before reaching 200 cycles at a confining pressure of 5 MPa. This is presumably because the electrolyte flowed due to the expansion and contraction of the negative electrode, and the substrate and the electrode came into contact. In the case of the short fiber reinforcement in Example 2, it is considered that the fluff came into contact with the electrode. In addition, in the case of the long fiber single layer in Example 3, it is presumed that the absence of a thin fiber layer caused the electrolyte substrate to lack integrity, and the electrolyte flowed with cycles, causing the spunbond layer to come into contact with the electrode, causing an increase in resistance, etc. In Examples 2 and 3, PET was used as the substrate, so the contact between the substrate and the electrode could be easily determined as a decrease in the discharge capacity retention rate without going through complicated processes such as impedance measurement, DC-IR measurement, and rate measurement. It was easily determined from the cycle test that a good interface can be maintained by controlling the pressure within the range of 1 MPa and 3 MPa.
[0145] [Composition analysis and consistency measurement] The cells of Examples 1 to 3 were disassembled, and the composition of the second electrolyte layer including the substrate was analyzed. It was found that the LiTFSI salt concentration in each cell was 0.9 mol / L, and the ratio of HNBR to acetonitrile was 1:1. The compositions of the cathode and anode were also similar. It is presumed that the above salt concentration was achieved as a result of acetonitrile being distributed to the cathode and anode. When the consistency of an ion-transporting organic material having the same composition as the second electrolyte layer including the substrate was measured, a value of 160 was obtained.
[0146] [Comparative Example 1] The same laminated nonwoven fabric as in Example 1 was prepared, and an ion-transporting organic material having the same composition as in Example 1 was applied by die coating. In Comparative Example 1, a back roll was arranged, the substrate was arranged vertically, and the die head was pressed from the side. The mixture passed through the nonwoven fabric, and it was confirmed that the back roll was wet with the mixture. The mixture was passed through a drying oven at 60 ° C. to obtain an electrolyte laminate having a total thickness of 26 μm, a substrate part of the laminated nonwoven fabric having a thickness of 20 μm, and an electrolyte layer having a thickness of 6 μm formed on one side of the substrate part. When the composition of the electrolyte layer not including the substrate part in this electrolyte laminate was analyzed, the cyano group ratio of HNBR and acetonitrile was 3:5, and the LiTFSI salt concentration was 0.75 mol / L.
[0147] The cathode and anode were prepared in the same manner as in Example 1, and the surface of the electrolyte laminate prepared in the above [Comparative Example 1] on which the 6 μm-thick electrolyte layer was formed was brought into contact with the anode side, and the laminate was sealed with an aluminum laminate film exterior body. The sealed body was then pressed at a temperature of 50° C. and a pressure of 1 MPa for 100 seconds. This resulted in a battery including a cathode / (LiTFSI:HNBR:PEO:acetonitrile) / anode element.
[0148] [Comparative Example 2] Fiber diameter 10μm, basis weight 6g / m 2 A 20 μm-thick polypropylene (PP) nonwoven fabric was prepared, and an ion-transporting organic material having the same composition as in Example 1 was applied by die coating in the same manner as in Comparative Example 1 to obtain an electrolyte laminate having a total thickness of 26 μm and a substrate part of the laminated nonwoven fabric having a thickness of 20 μm and a 6 μm-thick electrolyte layer formed on one side thereof. When the composition of the electrolyte layer not including the substrate part in this electrolyte laminate was analyzed, the cyano group ratio of HNBR and acetonitrile was 3:5, and the LiTFSI salt concentration was 0.75 mol / L.
[0149] As in Comparative Example 1, the surface of the electrolyte laminate produced in Comparative Example 2 above on which the 6 μm-thick electrolyte layer was formed was brought into contact with the anode side to obtain a battery including a cathode / (LiTFSI:HNBR:PEO:acetonitrile) / anode element.
[0150] [Comparative Example 3] Lithium hexafluorophosphate (LiPF6), polyacrylonitrile, and acetonitrile were mixed, and the LiPF6:polyacrylonitrile:acetonitrile mixture was applied to a laminated nonwoven fabric prepared in the same manner as in Example 1 by a die coater in the same manner as in Example 1. A back roll was not provided, the substrate was arranged vertically, and the die head was pressed from the side. The mixture passed through the nonwoven fabric, struck through the back, and it was confirmed that a coating film had been formed, and the nonwoven fabric was passed through a drying oven at 60°C. After passing through the drying oven, a release-treated film was attached to both sides of the film and rolled up. The coated nonwoven fabric was extracted and the composition was analyzed, and it was found that the cyano group ratio of acrylonitrile and acetonitrile was 1:9. The salt concentration was also 0.7 mol / L. In this way, an electrolyte laminate with a total thickness of 32 μm was obtained. It was confirmed that an electrolyte layer with a thickness of 6 μm was formed on both sides of the nonwoven fabric.
[0151] The cathode and anode were prepared in the same manner as in Example 1, except that the cyano group-containing hydrogenated nitrile rubber was replaced with polyacrylonitrile, and the electrolyte laminate prepared in the above [Comparative Example 3] was sandwiched between the anode and cathode, and sealed with an aluminum laminate film exterior. The seal was then pressed for 30 seconds at a temperature of 50°C and a pressure of 1 MPa. This resulted in a battery including a cathode / (LiPF6:polyacrylonitrile:acetonitrile) / anode element.
[0152] [Rate test, cycle test, impedance measurement] For the batteries obtained in Comparative Examples 1 to 3, conditioning, calculation of discharge capacity, rate test, and cycle test were carried out in the same manner as in the Examples.
[0153] In Comparative Example 1, the irreversible capacity was large at the conditioning stage and could not be measured. This is presumably because a side reaction occurred due to the PET substrate being in contact with the positive electrode. Cells in which the substrate and electrode are in contact should be removed early on because they will cause poor characteristics in non-liquid batteries, and the substrate was identified as an irreversible capacity at the first charge / discharge stage, and it can be evaluated as being easily determined without going through complicated processes such as impedance measurement, DC-IR measurement, and rate measurement.
[0154] In Comparative Example 2, PP was used as the substrate, but in this case, when a rate test was performed, only 50% of the capacity was obtained, and impedance measurement revealed that there was interface resistance. Since PP does not decompose, it was not possible to predict the results of the rate test or the impedance measurement at the initial charge / discharge stage.
[0155] In Comparative Example 3, the cycle characteristics were poor, and the more the cell's restraining pressure during charging and discharging was increased, the more severe the deterioration. This is thought to be because the electrolyte was deformed due to the large expansion and contraction of the negative electrode and the external restraining pressure, causing the base material to come into contact with the electrode. This is thought to be because polyacrylonitrile was used as the electrolyte, and its ratio was kept to 1 / 9 of acetonitrile, and the electrolyte had a low viscosity of 450. It was found that the electrolyte viscosity is important for non-liquid electrolytes, and the desired characteristics are expressed within an appropriate viscosity range.
[0156] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment. The present invention can be modified in various ways without departing from the gist of the present invention. [Explanation of symbols]
[0157] 100 Nonaqueous secondary battery 110 Exterior body 120 A region of the exterior body (expanded space) 130 Aluminum Tab 140 Nickel Tab 150 positive electrode 160 negative electrode 170 Electrolyte laminate (lithium ion conductor layer)
Claims
1. An electrolyte laminate comprising at least a first electrolyte layer, a second electrolyte layer, and a third electrolyte layer bonded and laminated in the order described above, the second electrolyte layer being a composite layer of an electrolyte and a base material formed of continuous long fibers, and each of the first, second, and third electrolyte layers containing an ion-transporting organic material, The first electrolyte layer and the second electrolyte layer contain different ion transporting organic materials, and the consistency of the ion transporting organic material contained in the second electrolyte layer at 25° C. is 100 or more and less than 400.
2. The electrolyte laminate of claim 1 , wherein the substrate is a laminated nonwoven fabric.
3. The laminated nonwoven fabric is composed of at least two laminated nonwoven fabric layers, including a nonwoven fabric layer (I layer) composed of fibers having a fiber diameter of 0.1 μm or more and less than 4.0 μm, and a nonwoven fabric layer (II layer) composed of fibers having a fiber diameter of 4.0 μm or more and 30.0 μm or less, and has a basis weight of 3.0 g / m. 2 20.0g / m or more 2 The electrolyte laminate of claim 2 , wherein the thickness is less than 100 nm.
4. The electrolyte laminate according to any one of claims 1 to 3, wherein the second electrolyte layer is a solid electrolyte layer, and a base material included in the solid electrolyte layer has a decomposition current threshold of 2.0 V or more and 4.5 V (vs. Li) or less.
5. The electrolyte laminate according to any one of claims 1 to 4, wherein the substrate is a continuous long-fiber nonwoven fabric or woven fabric composed of at least one selected from the group consisting of polyalkylene terephthalate resin, polyolefin resin, polyamide resin, polyoxymethylene ether resin, polyketone resin, thermoplastic polyimide resin, cellulose resin nonwoven fabric, glass nonwoven fabric, and glass cloth.
6. 6. The electrolyte laminate according to claim 1, wherein the ion transporting organic material contains a nitrile group.
7. The electrolyte laminate according to any one of claims 1 to 6, which is a solid electrolyte laminate.
8. An electrolyte film comprising the electrolyte laminate according to claim 7.
9. A non-aqueous secondary battery structure comprising a positive electrode, a negative electrode, and the electrolyte laminate according to any one of claims 1 to 7 or the electrolyte film according to claim 8, a nonaqueous secondary battery structure in which the first electrolyte layer or the third electrolyte layer is formed on the positive electrode, and one of the first electrolyte layer or the third electrolyte layer that is not in contact with the positive electrode is formed on the negative electrode, and the second electrolyte layer is self-supporting between at least one pair of the positive electrode and the negative electrode.
10. 10. A non-aqueous secondary battery comprising a positive electrode, the electrolyte laminate according to any one of claims 1 to 7 or the electrolyte film according to claim 8, and a negative electrode, laminated in the order listed.
Citation Information
Patent Citations
Lithium polymer cell
JP2003059535A
Lithium ion secondary battery
JP2014060123A
Method for manufacturing battery material, method for manufacturing electrolyte membrane, and battery material
JP2018032484A
Polymer electrolyte having a multilayer structure and all-solid-state battery including the same
JP2018514929A
Multilayered composite electrolyte for secondary batteries
JP2019510349A